Complete Genome Sequences of Classical Swine Fever Virus Subgenotype 2.1 and 2.2 Strains Isolated from Vietnamese Pigs - Kim, Ki-Sun (Microbiol Resour Announc, 2019)
Classical swine fever virus (CSFV) strains ND20 and HY78 were detected from infected pigs in the Xuan Truong-Nam Dinh and Hung Yen provinces in North Vietnam in 2014 and 2015, respectively. The most prevalent CSFV subgenotypes in Vietnam are 2.1 and 2.2, and these two complete genome sequences will help the CSFV prevention policy in Vietnam. In particular, subgenotype 2.2 (ND20 strain) has been reported less worldwide, so it is worth sharing information about this subgenotype.